The phylogenetic positions of Bhagadatta Moore, 1898, Kumothales Overlaet, 1940 and Harmilla Aurivillius, 1892 (Lepidoptera, Nymphalidae, Limenitidinae) based on molecular data - Niklas Wahlberg; Jana Maresova; Leidys Murillo-Ramos; Steve Collins; Li-Wei Wu (Nota Lepidopterologica, 2020)
We sequenced multiple genes from the enigmatic genera Bhagadatta Moore, 1898, Kumothales Overlaet, 1940 and Harmilla Aurivillius, 1892 (Nymphalidae, Limenitidinae) and analysed them together with a large published dataset. We find that Bhagadatta is sister to the genera Cymothoe Hübner, 1819+Harma Doubleday, 1848, and that Kumothales is sister to these three. Harmilla is nested within the genus Euriphene Boisduval, 1847. We thus transfer Kumothales and Bhagadatta to the tribe Cymothoini, and we synonymise Harmilla syn. nov. with Euriphene.